Efektivitas Pengelolaan Irigasi Oleh Kelompok Tani Padi Sawah di Kota Bengkulu - Restianingrum, Lika; Utama, Satria Putra; Susilo, Agung Tri; Emlan, Emlan (Jurnal MeA (Media Agribisnis), 2025)
This study aims to analyze the level of effectiveness of irrigation management by farmer groups and identify various factors associated with the level of effectiveness of irrigation management by farmer groups in Bengkulu City, especially in Singaran Pati, Sungai Serut, Gading Cempaka, and Selebar sub-districts. Data were collected through questionnaires distributed to 80 farmers using simple random sampling technique. Primary data were obtained from interviews and observations, while secondary data were collected from literature studies. This study used descriptive methods and Spearman correlation analysis to measure the relationship between variables. The results of the analysis show that the effectiveness of irrigation management by farmer groups in Bengkulu City is included in the medium category which is measured based on three variables namely the level of group cohesiveness, the level of group communication and member satisfaction on the effectiveness of irrigation management of wetland rice by farmer groups. Factors that have a significant relationship with the effectiveness of irrigation management in Bengkulu city are the level of unity, interpersonal needs, and member participation. While the quality of leadership, group awareness, and extension did not show a significant relationship. These findings are expected to provide insights for irrigation managers and stakeholders in improving irrigation management systems, as well as improving the welfare of farmers in rural areas.